The Influence of Social Media Marketing Through Celebrities on The Growth of Umkm in Makassar City - Putra, Taufan Eka; Imaduddin, Imaduddin; Ramlawati, Ramlawati (Jurnal Ekonomi, 2024)
This study aims to analyze the impact of marketing costs on net profit, with sales volume as an intervening variable, within culinary and fashion businesses in Makassar City that utilize celebrity endorsement services. The research method employed is field research with a quantitative approach, and data was collected through questionnaires. The study population includes all culinary and fashion businesses in Makassar City, with a sample of 44 businesses selected randomly through probability sampling. Data analysis was conducted using path analysis techniques with the aid of SPSS software version 26. The findings reveal that: (1) Marketing costs do not have a direct effect on net profit, (2) Marketing costs have a direct and positive effect on sales volume, (3) Sales volume has a direct and significant impact on net profit, and (4) Marketing costs indirectly influence net profit positively through sales volume.